Monitoring the agri-food system in Myanmar: Mechanization service providers – July 2022 survey round - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2022)
A phone survey was conducted in July 2022 to understand the effects of COVID-19 and political instability on Myanmar’s mechanization service providers (MSPs), crucial to enabling smallholder farmers to undertake a range of power-intensive farm and post harvest operations in a timely manner. This note reports on the results of this survey, the ninth in a series of phone surveys, as well as on trends from earlier surveys.